Planning for authentiCITIES. - (:unkn) unknown (Routledge, 2019)
Authenticity resonates throughout the urbanizing world. As cities' commercial corridors and downtowns start to look increasingly the same, and gentrification displaces many original neighborhood residents, inhabitants are left with a sense that their cities are becoming hollowed out, bereft of the multifaceted connections that once rooted them to their communities. And yet, in a world where change is unrelenting, people long for authentic places. This book examines the reasons for and responses to this longing, considering the role of community development in addressing community and neighbourhood authenticity.
Keywords: Stadtplanung; Stadtsoziologie; Planungsziel; Nachbarschaft; Erhaltende Erneuerung; Stadtraum; Authentizität; Zusammenleben; Gentrifizierung; Soziale Gerechtigkeit; Integrierte Planung; Soziale Mischung; Gemeinwesen